Transcriptomic and proteomic profiling of Actinobacillus pleuropneumoniae responses to iron starvation - Cui, Yifang; Chen, Jiahe; Feng, Xu; Guo, Fangfang; Shao, Yuxin; Xu, Fuzhou (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundActinobacillus pleuropneumoniae (APP) is the causative agent of porcine contagious pleuropneumonia, which remains a major pathogen endangering the swine industry. However, the mechanisms underlying its colonization and pathogenesis in pigs remain largely unknown.MethodsAn integrated analysis combining transcriptomic and proteomic profiling was employed to detect genetic and protein changes in APP under iron starvation.ResultsIn total, 458 differentially expressed genes (DEGs) from the transcriptome and 532 differentially expressed proteins (DEPs) from the proteome were identified. The comparative analysis showed that 137 differentially expressed genes/proteins were shared between DEGs and DEPs, with the majority exhibiting consistent regulatory changes at both transcription and protein levels. Functional enrichment analysis revealed that the downregulated genes were predominantly associated with the generation of precursor metabolites and energy (45/105, 42.86%), primary metabolic process (29/105, 27.62%), ion binding (20/105, 19.05%), and metal cluster binding (18/105, 17.14%), corresponding to pathways involved in primary metabolites and energy biosynthesis and cellular respiration. Conversely, the upregulated genes were primarily enriched in iron transport (11/30, 36.67%) and iron binding (9/30, 30%), which corresponded to the iron starvation conditions. The expression changes of iron utilization systems, including TonB-ExbB-ExbD and some TonB-dependent receptors, by qRT-PCR were consistent with the results in both transcriptome and proteome analyses.ConclusionThis study provided a global perspective on the response mechanisms employed by APP to iron starvation, characterized by suppressing electron transport and energy metabolism pathways and upregulating the pathways associated with the TonB-ExbB-ExbD energy transduction system for iron acquisition.